Utilization of Environment-Based PAI Learning Resources - Ahmad Mahfuzi (Syntax Corporation Indonesia, 2023)
In the current context, learning activities have been greatly facilitated by the existence of various kinds of learning resources that can be used as a reference for exploring knowledge in order to improve and enrich our insights so that we can respond to the challenges of globalization. And one of the learning resources that can be utilized by humans is the environment. The environment is one source of learning that has a broad scope. And basically, all types of environment, around children can be used to optimize educational activities as long as they are relevant to basic competencies and learning outcomes. Based on its origin, the learning environment can be divided into three types, namely: the original natural environment, the man-made environment and the social environment. The environment does have a very important role as a source of learning, where learning from the environment is expected that students will directly experience learning from the experiences they get. Therefore, learning in the environment provides several benefits including: learning activities are more interesting, the nature of learning will be more colorful, the materials studied will be richer, learning activities will be more comprehensive, there will be more learning resources, students can understand and live up to these aspects. life in the environment.